Educazione e persona. Prospettive pedagogiche tra ricerca di senso e nuovo umanesimo - Bossio, Francesco (Studi sulla Formazione/Open Journal of Education, 2018)
The person takes form in a unique and unrepeatable way combining his developmental potential with the circumstances of existence. During this process, He is continually inclined towards the relationship with the other. Education, in all its forms, is today a real human and social need, it is an inescapable paradigm for reconnecting man to himself by orienting him towards paths of existential awareness and authenticity, it is, also, a paradigm capable of renewing society from within through ethical projects aimed at the common good.